BIOMASS OF GREEN SOYBEAN CULTIVARS IN CULTIVATION SYSTEM WITH CORN - VIANA, Jeandson Silva; BRUNO, Riselane Lucena Alcântara; SANTOS, Hemmannuella Costa; SILVA, Ivandro França; OLIVEIRA, Ademar Pereira; BRAGA JÚNIOR, Joel Martins (Scientia Agraria, 2009)
The soybean is an important producing leguminous of grains of the Brazil, contributing for the chemical characteristics of the ground with the nitrogen setting of air, by means of the association with bacteria of soil and supply of biomass, mainly when in trust with the corn. The research was performed in field conditions at the “Centro de Ciências Agrárias da Universidade Federal da Paraíba, Areia-PB” to evaluate the effect of cultivation systems, with or without inoculation, production of biomass of the green beans of soybean cultivars in the green stage. The experimental design was distributed in random blocks, in sub-subdivided plots (3 x 2 x 2), with three cultivars (Pati, JLM 004 and Pirarara), with and without inoculation and in intercrop and monoculture systems, with four replications.Cultivars Pirarara and Pati produce more root biomass in the intercrop; the cultivation system with inoculate in interaction with cropping provides greater accumulation of biomass of roots and shoots of soybean plants, compared with the without inoculation; the inoculation nodules provides in greater numbers in the roots of soybean plants.